PENGARUH PENGGUNAAN TEKNIK MIND MAPPING TERHADAP KETERAMPILAN MENULIS TEKS PERSUASIF - Sadilla, Fenny Gina; Tressyalina, Tressyalina; Hafrison, Mohammad (Universitas Negeri Padang, 2018)
ABSTRACTÂ The purpose f this research are (1) To know the students class VIII at SMP Negeri 11 Padang ability to write persuasive text without using mind mapping technique. (2) To know the students class VIII at SMP Negeri 11 Padang ability to write persuasive text using mind mapping. (3) To analyze the effects of using mind mapping technique towards students ability to write persuasive text class VIII at SMP Negeri 11 Padang. This is qualitative research using quasi experiment. Based on data analysis, using mind mapping technique affects to students class VIII SMP Negeri 11 Padang ability to write persuasive text.Â Kata kunci: pengaruh, teknik mind mapping, menulis teks persuasif